ANALYSIS AND EVALUATION OF EDUCATIONAL MATERIALS IN TEACHING FOREIGN LANGUAGES - Xakimova Munira Xabibullayevna; Turmuhammadova Sevinch Akmal qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   Article  presents  a  comprehensive  analysis  and  evaluation  of  educational materials used in the teaching of foreign languages. It explores the criteria for selecting effective  materials,  including  authenticity,  cultural  relevance,  and  alignment  with learners' needs and goals. The study emphasizes the importance of integrating diverse resources,  such  as  textbooks,  digital  tools,  and  multimedia  content,  to  enhance language acquisition and engagement. Additionally, it examines the role of teachers in adapting and supplementing materials to cater to different learning styles and contexts. By  assessing  various  types  of  educational  resources,  this  research  aims  to  provide insights into best practices for language instruction and the development of effective curricula.